The covenant of genesis eaudiobook A novel. - McDermott, Andy (Nina Wilde and Eddie Chase, 2011)
AN INCREDIBLE DISCOVERY. A MERCILESS FOE. A DEADLY RACE FOR THE TRUTH. Off a remote stretch of the Indonesian coast, archaeologist Nina Wilde has made an astounding discovery: an artifact that will rewrite everything that's known about human history. But before she can return to tell the world of her find, her ship is brutally attacked, her crew is ruthlessly murdered, and the artifact is stolen. Someone wants this secret to stay hidden—and will do anything to keep it that way. From the depths of the ocean to the Australian outback, to the halls of the United Nations, Nina and her fiancé, ex-SAS bodyguard Eddie Chase, embark on a quest to stop the all-powerful Covenant of Genesis, a clandestine group sworn to keep Nina's discovery a secret. Nina and Eddie have faced tough adversaries before, but the relentless Covenant is always two steps ahead of them—and more than willing to kill again. Who will be the first to expose the truth—and the first to claim the most valuable archaeological prize of all time?